PERTUMBUHAN TANAMAN JELUTUNG RAWA (Diera lowii) DI LAHAN RAWA GAMBUT KABUPATEN PULANG PISAU, KALIMANTAN TENGAH (Growth of Jelutung rawa (Diera lowii) at the Peat Swamp Land in Pulang Pisau District, Cetral Kalimantan) - Wahyudi; Triyadi, Antonius (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2019)
Plantation of jelutung rawa (Diera lowii) project has been conducted by many local peoples, aspecialy at the Pulang Pisau District, Central Kalimantan. The purpose of this research was to analyze the growth of Jelutung rawa (Diera lowii) at the Peat Swamp Land in Pulang Pisau District, Cetral Kalimantan. The research was conducted at Jabiren Village, Pulang Pisau Disttrict, Central Kalimantan start from July to September 2019. Researct result showed that mean annual increment (MAI)-diameters of jelutung rawa at 4, 6, 7, 10, 12 dan 13 years old namely 2.52 cm-2, 2.52 cm-2, 2.80 cm-2, 2.22 cm2 , 2,14 cm-2 and 2,02 cm-2 respectively. Meanwhile, at the same of ages, height of jelutung rawa namely 4.88 m, 6.50 m, 10.84 m, 11.29 m, 16.17 m, and 19.30 m respectively. Polynomial growth model of jelutung rawa for their diameter and height are y = - 3.825941 + 4.1244995x + (-0.140316) x 2 and y = 3.562047 + 0.212857x + 0.72187x2 respectively with coefficient of determination namely 62% and 82% respectively.